The Role of a Variety of Research Studies on Problem Management - Djatmiko, Budi; Galinium, Maulahikmah; Lutfiani, Ninda (APTISI Transactions on Management (ATM), 2018)
In the process of finding the truth, factual information is needed, starting from simple methods such as good time management in reading, listening and asking questions, until complex ways of research. So, researchers must understand what types of research can be used as references, to facilitate researchers in doing problem management properly, the results of which are able to solve problems and obtain factual information. This paper describes 7 (seven) different types of research, there are research based on approaches, functions, purpose, characteristics, problem characteristics, research process, and measurement techniques and data analysis. The explanation’s purpose of the variety of research is to provide insight into the management of the problems that occur with the planning carried out by the researcher, especially in terms of literature, so that before considering various stages of planning and doing research, researchers can also consider the main features of certain forms of research that are well compiled and reported. So, problem management can be done as well as possible to produce valid steps in solving problems. Keywords : Variety of Research, Literature, Factual Information, Problem Management